Public Health Information Behavior at Flood-Prone Area In Bandung Regency: A Case Study in Baleendah Village, Andir Village, Bojongsoang Village and Dayeuh Kolot Village - Kurniasih, Nuning; Sukaesih, Sukaesih (Record and Library Journal, 2017)
This study aims to understand the public health information behavior in the vicinity of flood prone area by examining 1) The public health information behavior in identifying diseases that may occur because of a flood. 2) The information behavior in finding health information solution required for dealing with diseases that may occur because of a flood. 3) The public health information behavior in determining health information sources which is used. 4) The public health information behavior in making use of health information for diseases that may occur because of a flood. 5) The public health information behavior in making use of health institution to satisfy its information needs. 6) The public health information behavior in flood prone area. The method used in this research is qualitative method supported by Case Study approach. In this research, we analyze data obtained from Focus Group Discussion (FGD) conducted by 11 informants and in-depth interview with 20 interviewees that are competent with this research research for triangulation. The result of this research reveals that people living in the flood prone area vicinity in Baleendah Village, Andir Village, Dayeuh Kolot Village and Bojongsoang Village, Bandung Regency (1) identify the potential of a flood disease based on their experience and identification during a flood (2) search for health information solution required for overcoming disease potential because of a flood by asking directly to a doctor or health center staff or volunteers during a flood. For psychological problem, usually people consult with religious leader, although Social Agency provice service to overcome this problem. (3) The main information source used is one that is informed by the health center or village midwife. (4) People use health information to help healing process when they get sick during the disaster. Health information obtained when a flood does not happen is only for adding insights. (5) Health Agency through health center and village midwife are actively involved to give health counseling to the public on various occasions. Those five things influence The public health information behavior in the flood prone area.